Cortés Zavala, María Teresa. Social Order and public health in Puerto Rico, 19th century. A view from cultural history. Morelia, Michoacán: Universidad Michoacana de San Nicolás de Hidalgo, Historiadores de las Ciencias y las Humanidades, 2017, 154 p. (2020)
Reseseña